Legal Construction of the Buginese Understanding - Muhammad Yusuf; Ismail Suardi Wekke; Afandi Salleh; Rosdalina Bukido (Jurnal Ilmiah Al-Syir'ah, 2021)
This article investigates the relevance of values of Bugis culture dan Muslim Scholars' views in Bugis Quranic exegesis by MUI of South Sulawesi. This research uses a content analysis approach to the Bugis Quranic exegesis. Bugis Muslims scholars' views about women's rights (opportunity) to be public leaders, iddah, and inheritance distribution are relevant to core values of Bugis culture and local wisdom of Bugis people. To be public leaders, women never mind as long as they fulfill qualitative and functional criteria. In household affairs, a married couple is a partnership where both have responded to do together. 'Iddah stress to religious principle and culture of siri' (self-respect), paccing (purity), asitinajang (fairness).  Inheritance distribution does relate to the right and responsibility to realize equality and justice. Muslim scholars' of Bugis have the expertise to deliver values of Bugis culture, and explanatory is not only explicitly, but also implicitly and inherently. The Quran and local wisdom are two values integrated into giving solutions to people. Therefore, the integration between local wisdom relevant to the teachings of Islam (the Koran) undertaken by the ulama will undoubtedly be more effective.